“Got Faith?” The Integration of Muslims in the Netherlands / “¿Tiene fe?”. La integración de los musulmanes en Holanda - Elfersy, Daphna (Araucaria, 2014)
The retreat of multiculturalism in the Netherlands has been accompanied by the unwavering demand for the ’better’ integration of Muslim citizens. In former times, the success of integration was identified in the closing of linguistic, economical and educational gaps between society and newcomers. However, in recent years, the notion of integration has become synonymous with the process of secularization. Thus, Muslims’ affiliation to the Islamic faith is largely seen as a sign of impaired integration. This article examines the integration process of Dutch Muslims by the ’old’ socioeconomic and ’new’ faith-related integration-criteria from a critical point of view. This study explores the differences in the socioeconomic status and religious beliefs of Muslims and non-Muslims in the Netherlands and provides a new approach to the perceived gap between the ’believing’ Muslims and ’secularized’ Dutchmen. It suggests that the Dutch’s intertwinement of the integration process with the process of secularization overlooks the persistent ’irrationality’ and even rising belief in the de-churched Dutch society. It finds that Dutch Muslims and non-Muslims display certain differences but also surprising similarities in their engagement with faith.